Research on the performance of plate and roll capacitor deionization devices based on supercapacitor carbon electrodes(基于超级电容活性炭电极的板式与卷式电容去离子装置的性能研究) - 翁琦辉(WENG Qihui); 陈涵(CHEN Han); 贺斯佳(HE Sijia); 张燚(ZHANG Yi); 杨岳平(YANG Yueping) (Zhejiang Daxue xuebao. Lixue ban)
Capacitive deionization is an energy-saving and environmentally friendly brackish water desalination technology. The performance of capacitive deionization is influenced by two significant factors: electrode materials and device configurations. Three types of commercially available supercapacitor carbons AC1, AC2, and AC3 were used to characterize and optimize them for electrode production. The results demonstrate that AC2 activated carbon exhibits the highest specific surface area (1 908.4 m2·g-1) and specific capacitance (67.8 F·g-1). And AC2's internal pore resistance is also the lowest. Therefore, AC2 was chosen as the electrode material to study the operation of plate and roll devices under different experimental conditions. The optimal working voltage of the two configurations was 1.6 V, the temperature was 25 ℃, the optimal flow rate of the plate device was 60 mL·min-1, and for the roll device it was 360 mL·min-1. Under the optimal working conditions, the desalination amount per unit area and current efficiency of the roll device are 1 569.7 mg·m-2 and 46.7% respectively, much bigger than 696.5 mg·m-2 and 11.3% of the plate device. These results indicate that the roll device outperforms the plate device in terms of desalination performance and charge efficiency.(电容去离子是一种节能环保的新兴盐水淡化技术，电极材料与装置是影响电容去离子性能的两大重要因素。分别对3种市售超级电容活性炭AC1、AC2、AC3进行表征并择优开展后续实验，结果表明，AC2活性炭的比表面积与比电容最大，分别为1 908.4 m2·g-1和67.8 F·g-1，内部孔隙电阻最小。因此，以AC2为电极材料研究板式与卷式电容去离子装置在不同实验条件下的运行情况，发现2种装置的最佳工作电压均为1.6 V、温度均为25 ℃，最佳流速，板式装置为60 mL·min-1，卷式装置为360 mL·min-1。在最佳工作条件下，卷式装置的单位面积脱盐量与电荷效率分别为1 569.7 mg·m-2和46.7%，远大于板式装置的696.5 mg·m-2和11.3%，卷式装置具有更强的脱盐性能与能量利用率。)